Gelatin-stabilized traditional emulsions: Emulsion forms, droplets, and storage stability - Mengzhen Ding; Ting Zhang; Huan Zhang; Ningping Tao; Xichang Wang; Jian Zhong (Food Science and Human Wellness, 2020)
Fish oils are important substances in the field of food and drug delivery. Due to their unstable double bonds, fishy taste, and poor water solubility, it is pivotal to investigate novel dosage forms for fish oils, such as encapsulated droplets. In this work, we primarily prepared gelatin-stabilized fish oil-loaded traditional emulsions and investigated their emulsion forms, droplets, and storage stability under different preparation and storage conditions. Our results showed that higher gelatin solution pH, higher storage temperature in the range of 4–37 °C, and increased storage time induced the emulsion form switch from a liquid form to a redispersible gel form of the fish oil emulsion. The droplets had core-shell microstructures and a trimodal size distribution, which decreases linearly with increasing gelatin solution pH and homogenizing time, but decreases exponentially with increasing homogenizing speed. In addition, storage temperature showed a notably different effect on traditional emulsion storage. This work provides a fundamental knowledge for the formation, microstructure, and properties of gelatin-based traditional emulsions. It also provides a promising new application for fish oil-loaded emulsions in food beverages, soft candy, and other food products.